John C. Babcock papers - Babcock, John C., 1836-
Principally correspondence (1855-1865, 1902-1908) relating to Babcock's service in the military intelligence bureau of the Army of the Potomac. Correspondents include Winfield Scott Hancock, Theodore Lyman, George Gordon Meade, Marsena Rudolph Patrick, William A. Pinkerton, and Henry Augustus Sharpe.
Army officer and architect.
Collection material in English.
Keywords: Hancock, Winfield Scott, -- 1824-1886 -- Correspondence; Lyman, Theodore, -- 1833-1897 -- Correspondence; Meade, George Gordon, -- 1815-1872 -- Correspondence; Patrick, Marsena Rudolph, -- 1811-1888 -- Correspondence; Pinkerton, William A. -- 1846-1923 -- Correspondence; Sharpe, Henry Augustus, -- 1848-1919 -- Correspondence; United States. -- Army of the Potomac; Military intelligence; Architects; Army officers